Surface and underground flooding of soils and lands in central Russia - N. V. Razumova; V. V. Razumov; E. N. Molchanov (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The authors systematized and comprehensively analyzed the different sources containing the information on surface and underground flooding of soils and lands at the territory of Central Russia. The above processes are observed through their intensive manifestation within the zones of soddy-podzolic, gray forest soils and chernozems in Tver’, Smolensk, Moscow, Ryazan’, Bryansk, Voronezh, Kursk, Tambov, Yaroslavl, Kaluga regions of the studied territory. It is shown that natural events and those induced by human interventions serve as a reason for ccurring and developing these processes in different regions. The soils reveal short-duration flooding and become even waterlogged due to frequent and heavy rainfalls and spring floods taken place almost every year. However, the soils are becoming excessively wet for a long period of time resulted from the groundwater rise due to water engineering constructions and the irrational land use. Being affected by natural and anthropogenic factors, the constant wetting (water-logging and underground flooding) can be also as a consequence of intense urban building accompanying by drainage destruction of the ground water. Special attention is paid to elaborating a complex of measures to prevent the adverse effects of such dangerous natural processes.